2009
DOI: 10.1002/aic.11979
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mixer properties and fill level on granular flow in a bladed mixer

Abstract: in Wiley InterScience (www.interscience.wiley.com).The discrete element method was used to study the effect of mixer properties and fill level on the granular flow of monodisperse, cohesionless spheres in a bladed mixer. For fill levels just covering the span of the blades, a three-dimensional (3-D) recirculation zone develops in front of the blades, which promotes vertical and radial mixing. Increasing fill level reduces the size of the recirculation zone, decreases bed dilation and hinders particle diffusivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 32 publications
6
58
0
Order By: Relevance
“…The limited blade speed dependence is reasonable considering that the particle-particle and particle-wall interactions depend on their relative velocities, not the absolute velocities. As has been found in previous studies (e.g., Remy et al, 2010), the internal particle stresses are more influenced by the weight of the supported material.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The limited blade speed dependence is reasonable considering that the particle-particle and particle-wall interactions depend on their relative velocities, not the absolute velocities. As has been found in previous studies (e.g., Remy et al, 2010), the internal particle stresses are more influenced by the weight of the supported material.…”
Section: Discussionmentioning
confidence: 55%
“…17. The mean and median of the max(|Ļƒ 1 |, |Ļƒ 3 |) distributions increase with dimensionless bed height, as is expected since it has been observed that the stresses in an AFD geometry are due largely to the weight of the material in the device (Remy et al, 2010). The fitting parameter b is nearly independent of H/H B and approximately equal to 0.5, and the parameter a decreases in a nearly linear manner with increasing H/H B .…”
Section: Influence Of Bed Depthmentioning
confidence: 55%
“…Since it is well known that the filling protocol of blenders has a strong impact on mixing performance, we performed lab-scale mixing experiments with different powder filling sequences and fill levels. Furthermore, we analyzed experimentally the convective and diffusive mixing properties of the binary pharmaceutical powder blend based on recent simulation studies of the mixing process [39].…”
Section: Introductionmentioning
confidence: 99%
“…Overcoming the problems associated with differences between calibration and measurement has been discussed in the literature (20,21). Moreover, the dynamics of blending processes have been studied theoretically as well (22,23) and experimentally using model substances (24) and pharmaceutical powders (25). However, using one probe in the same position usually does not provide a reliable assessment of the blending process (21,26).…”
Section: Introductionmentioning
confidence: 99%